Cybercrime : the invisible threat - Sadre, Hossein; Gibbons, Jim; Way Press International Productions; Films for the Humanities (Firm) (Princeton, NJ : Films Media Group, 2004)
Examines the Internet's exponential growth and evaluates risks posed by groups and individuals bent on crime or terrorism. Experts from the FBI, the Pentagon, and private companies, and even a self-confessed hacker comment on the danger of online fraud and denial of service attacks as well as on anti-hacking and biometric identification as ways of pretecting the World Wide Web--and perhaps the world itself
Jim Gibbons, narrator
DVD format
Keywords: Computer crimes